Ecdysone pathway is required for furrow progression in the developing Drosophila eye. - Brennan, C.A.; Ashburner, M.; Moses, K. (Development, 1998)
In Drosophila, secretion of the steroid hormone ecdysone from the prothoracic ring gland coordinates and triggers events such as molting and metamorphosis. In the developing Drosophila compound eye, pattern formation and cell-type specification initiate at a moving boundary known as the morphogenetic furrow. We have investigated the role of ecdysone in eye development and report here that the ecdysone signaling pathway is required for progression of the morphogenetic furrow in the eye imaginal disc of Drosophila. Genetic disruption both of the ecdysone signal in vivo with the ecdysoneless1 (ecd1) mutant and of ecdysone response with a Broad-Complex mutant result in disruption of morphogenetic furrow progression. In addition, we show that ecdysone-dependent gene expression, both of a reporter of transcriptional activity of the Ecdysone Receptor and of the Z1 isoform of the Broad Complex, are localized in and close to the furrow. These results suggest that, in the morphogenetic furrow, temporal hormonal signals are integrated into genetic pathways specifying spatial pattern.